PENGARUH UMUR, KEPERCAYAAN DAN SISTEM INFORMASI TERHADAP KINERJA INDIVIDUAL - Kesaulya Juliana; Srimusaid Srimusaid (Politeknik Negeri Lhokseumawe, 2016)
This study aimed to analyze the influence of age, user confidence and information systems onindividual performance. This study uses aquantitative method where the data obtained from thequestionnaire with purposive sampling method. Results from this study areas follows: (1) age, and nosignificant effecton the performance ofthe individual, which means that ageis not adifferentiatingfactor in terms of enhancing individual performance. (2) user confidence and significant effecton theperformance of the individual, whichmeans that if the user confidence in information technology isused, then the individual's performance will increase. (3) the information system and significantimpacton the performance ofthe individual, which means better and more effectively used systemwhich will improve the performance of individuals.Keywords: Age, User Trust, Information Systems, Individual Performance